An Enigmatic Case of Jaundice and Photosensitivity in an Adolescent. Issue 2 (4th February 2023) - Bhagat, Naveen; Singh, Pranjal; De, Arka; Mitra, Suvradeep; Kumar, Ashwani; Dhanasekaran, Venkatesh; Parkhi, Mayur Vilas; Ray, Debadrita; Duseja, Ajay
ABSTRACT: Erythropoietic protoporphyria (EPP) presents with nonblistering photosensitivity. Hepatobiliary manifestations are seen in around 5% cases and include cholelithiasis, elevations in liver enzymes, progressive jaundice, and end-stage liver disease. The diagnosis is suspected based on clinical features and elevated erythrocyte metal-free protoporphyrin and confirmed by genetic analysis showing loss-of-function mutations in the ferrochelatase (FECH) gene. We present an adolescent boy who presented with jaundice and photosensitivity with the liver biopsy showing deposition of brown pigments within the canaliculi and hepatocytes. This pigment showed Maltese cross birefringence on polarizing microscopy and Medusa-head appearance on electron microscopy. Genetic analysis revealed loss-of-function mutations in FECH. Introduction of EPP is an inborn error of heme biosynthesis caused by mutations in FECH with a prevalence of 1:75, 000 to 1:200, 000. We present a case of a 16-year-old adolescent boy with photosensitivity, abdominal pain, and jaundice with protoporphyrin deposition in the liver who was ultimately diagnosed with EPP based on genetic analysis.